Ethyl Acetate Extract of Elsholtzia bodinieri Vaniot Attenuates Oxidative Stress in ALI Mice - Yin H; Hu J; Li Y; Feng Y; Li Z; Sun R; Tian L; Li Y (Journal of Inflammation Research)
Haiaolong Yin,1,* Jianhua Hu,2,* Yaxian Li,1 Yi Feng,1 Zhiwei Li,1 Rongyan Sun,1 Lei Tian,1 Ye Li3 1Faculty of Food Science and Engineering, Kunming University of Science and Technology, Kunming, 650500, People’s Republic of China; 2Department of Orthopedic Surgery, the First People’s Hospital of Yunnan Province, the Affiliated Hospital of Kunming University of Science and Technology, Kunming, 650500, People’s Republic of China; 3School of Medicine, Kunming University of Science and Technology, Kunming, 650500, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lei Tian, Faculty of Food Science and Engineering, Kunming University of Science and Technology, Kunming, 650500, People’s Republic of China, Email leotian@kust.edu.cn Ye Li, School of Medicine, Kunming University of Science and Technology, Kunming, 650500, People’s Republic of China, Email liye918@gmail.comPurpose: Acute lung injury (ALI) is a serious clinical respiratory disease, but there are few effective drugs for ALI. As a natural product, Elsholtzia bodinieri Vaniot is used as a drink and medicine in ethnic minority areas of Southwest China. In previous studies, we found that E. bodinieri Vaniot methanol extract (EBE) was effective against ALI. This study was carried to investigate the role and mechanisms of EBE ethyl acetate extract (EBEE) against oxidative stress in ALI.Methods: By multiple bioinformatics analysis, AGER and ITGB2 were found to be the potential target genes of EBEE against oxidative stress in ALI. Different doses of EBEE were feed into ALI mice in vivo (600 mg/kg bw, 200 mg/kg bw) and .RAW 264.7 cells (100 μg/mL, 25 μg/mL) in vitro to evaluate the protection function. Western Blot, immunofluorescence and biochemical factor detection were used to measure the levels of oxidative stress associated factors, and gut microbiota analysis examined the gut microbiota in mice.Results: EBEE, which contained a total of 1374 components, was identified as the most active against oxidative stress. The EBEE treatment most significantly downregulated the ROS, MDA and pathological damages. AGER and ITGB2 were picked up as target genes of EBEE against ALI by bioinformatics. In vitro and in vivo, AGER, NOX4, and P-GSK3β expression levels were significantly decreased, and ITGB2, P-AKT, NRF2 and HO-1 were significantly up-regulated throughout EBEE treatment. By consuming EBEE, Chthoniobacteraceae significantly increased, while the pernicious bacteria Staphylococcaceae significantly reduced in ALI mouse.Conclusion: EBEE treatment significantly ameliorated the pathological damage and oxidative stress by regulating AGER, ITGB2 and related pathways in vitro and in vivo. Furthermore, EBEE treatment improved the composition of the gut microbiota in ALI mice. These data suggested that EBEE could be used as a potential functional food for prevention and treatment of ALI.Keywords: Elsholtzia bodinieri Vaniot, ethyl acetate extract, acute lung injury, oxidative stress, AGER, ITGB2